Effectiveness of cartoons for children's procedural pain: a systematic review with meta-analysis. - Luca Giuseppe Re; Massimiliano D'Elia; Vincenza Aloia; Stefania Celeste Rippa; Valentina Tommasi (Milano University Press, 2024)
BACKGROUND: Cartoons are widely used distraction techniques for nonpharmacological management of procedural pain in pediatric settings. There are a few studies in the literature evaluate the effect of intervention on procedural pain, but a systematic review aimed at providing a summary of the overall effect is lacking. AIM: To summarize the available evidence on effectiveness of cartoons for children's procedural pain. METHODS: Searching for parallel-group controlled trials was carried out on thirteen biomedical databases, five trial registries, web resources and gray literature sources from each database or resource setup date to 22 January 2023. Primary outcome was procedural pain, secondary outcome was anxiety. RoB 2 and ROBINS-I were used to assess risk of bias of included studies. RESULTS: 24 trials were selected for this review, which included a total of 3046 pediatric subjects. Children who watch cartoons during medical procedures experience less pain (SMD= -1.29; 95% CI: -1.75, -0.83; N=2239) and anxiety (UMD= -1.75; 95% CI: -2.94, -0.56; N=552) compared to children provided standard of care; for both outcomes, results are statistically significant. GRADE method shows moderate certainty/quality of evidence. CONCLUSIONS: Cartoons are more effective than standard of care in reducing procedural pain and anxiety in children. Pending future studies confirming the results, we recommend their implementation in daily clinical practice even in care settings with limited resources.